A case report of a late left atrial appendage perforation 4 months after occluder implant: reason for or caused by a resuscitation?. Issue 4 (4th October 2019) - Schenke, Karsten; Geidel, Stephan; Keller, Christian; Grönefeld, Gerian
Abstract: Background: Atrial fibrillation (AF) is a common disease and can lead to cardioembolic stroke. Stroke prevention according to the CHA2 DS2 VASc score is achieved via oral anticoagulation. In recent years, interventional occlusion of the left atrial appendage (LAA) has become a common alternative. Besides showing non-inferiority in large trials compared with warfarin interventional LAA occlusion can lead to serious adverse events with most of them occurring peri-interventionally. Case summary: A 75-year-old man with AF and recurrent gastrointestinal bleedings was referred for an interventional closure of the LAA. The intervention was successful with an ABBOTT ® Amulet device. Four months later, the patient had to be resuscitated. Return of spontaneous circulation occurred after 10 min. On hospital arrival, echocardiography revealed a pericardial tamponade and 2 L of blood were drained. A coronary angiogram revealed a lesion with active leakage of contrast agent in the proximal circumflex artery. The patient was transferred to the cardiac surgery department immediately. Intra-operatively a perforation of the tissue at the basis of the LAA close to the left main coronary artery was discovered. The occluder was excised and the LAA was closed by endocardial sutures. Discussion: In this report, we review the literature concerning interventional LAA occlusion and the reported cases of LAA perforation. Retrospectively, it remains unclear whether the perforation caused the resuscitation or was induced by it. To our knowledge, this is the first reported case of a laceration of a coronary artery by an occlusion device.